291. Effect of Previous Antibiotic Exposure on the Yield of Bone Biopsy Culture in Patients With Osteomyelitis. (26th November 2018) - Simms, Andrew; Fey, Paul D; Lyden, Elizabeth; Hewlett, Angela; Rupp, Mark E
Abstract: Background: Bone biopsy and culture are gold standards for the diagnosis of osteomyelitis and are key factors in defining the etiology and treatment of osteomyelitis. There is concern that recent antibiotic exposure will decrease the sensitivity of microbiologic cultures. Methods: A retrospective analysis was performed of patients who underwent bone biopsy for evaluation of osteomyelitis at the University of Nebraska Medical Center from 2014 to 2017. Microbiological culture data were compared with the number of days of antibiotic treatment the patient received prior to biopsy. Days of antibiotic use was divided into quartiles and the Cochran-Armitage test was used to test whether antibiotic exposure was associated with culture yield. Fisher's exact test and the Mann–Whitney test were used to compare anatomic location, diagnostic method, tobacco use, median WBC, ESR, CRP with culture positivity. Multivariable logistic regression was used to determine independent predictors of culture positivity. Results: A total of 211 patients were studied. Descriptive statistics: 63% male, 85% Caucasian, median age: 55 years, duration of osteomyelitis prior to biopsy: median 39 days (mean 139 days). Location of osteomyelitis: lower extremity 48%, sacral/pelvic 19%, skull/facial 12%, spine 11%, upper extremity/chest 9%. Within 2 weeks prior to biopsy, the median value of the maximum WBC count, ESR, and CRP was 10.5, 66, and 5.7, respectively. A significant negative linear trend between culture positivity and days of antibiotic exposure ( P < 0.0001) was observed (Figure 1). The rate of culture positivity was 85.07% for patients diagnosed with osteomyelitis who did not receive antibiotics and dropped to 78.57%, 73.08%, and 50% for patients who received 1–3 days, 4–14 days, and >14 days of antibiotics, respectively. Other independent predictors of culture positivity included elevated CRP ( P = 0.0017) and clinical diagnosis of osteomyelitis (vs. histologic or radiographic) ( P = 0.0042). Conclusion: There is a clear negative linear correlation between pre-bone biopsy antibiotic exposure and culture positivity in patients diagnosed with osteomyelitis. In addition, elevated CRP and method of osteomyelitis diagnosis independently correlate with culture positivity. Disclosures: All authors: No reported disclosures.